A Review on the EnteroMix Vaccine for Targeted Cancer Treatment: Review Article (Journal of Pharma Insights and Research, 2025)
EnteroMix vaccine is a significant development in the field of therapeutic oncology, departing from conventional non-specific cytotoxic treatments toward highly precise, multi-modal immunotherapy. This dual-platform technique combines engineered oncolytic enteroviruses with a personalized messenger RNA (mRNA) component to address the challenges of tumor heterogeneity and the immunosuppressive microenvironment. By leveraging the natural tropism of specific viral vectors to colonize and lyse malignant cells, the vaccine initiates an immediate innate immune response through the release of damage-associated molecular patterns and endogenous antigens. Simultaneously, the inclusion of patient-specific mRNA, derived from the unique mutational environment of the individual’s tumor, directs the adaptive immune system toward neoantigens that are absent in healthy tissues. Preliminary clinical observations indicate high rates of immunogenicity and significant reductions in tumor volume, particularly in gastrointestinal and dermatological malignancies. The synergy between viral-mediated "heating" of immunologically cold tumors and the precision of mRNA-encoded CTL priming suggests a robust mechanism for overcoming immune evasion. This approach not only promotes acute tumor regression but also provides long-term immunological memory, potentially reducing the risk of disease recurrence. As clinical trials progress into later phases, the evaluation of systemic safety, scalability of personalized manufacturing, and long-term survival outcomes remains vital. The current evidence positions this hybrid technology as a viable candidate for the next generation of targeted cancer therapeutics, bridging the gap between broad-spectrum viral therapy and individualized genomic medicine.